Evaluation of the effects of focused ultrasound stimulation on the central nervous system through a multiscale simulation approach - Scarpelli, Alessia; Stefano, Mattia; Cordella, Francesca; Zollo, Loredana (Frontiers in Bioengineering and Biotechnology, 2022)
The lack of sensory feedback represents one of the main drawbacks of commercial upper limb prosthesis. Transcranial Focused Ultrasound Stimulation (tFUS) seems to be a valid non-invasive technique for restoring sensory feedback allowing to deliver acoustic energy to cortical sensory areas with high spatial resolution and depth penetration. This paper aims at studying in simulation the use of tFUS on cortical sensory areas to evaluate its effects in terms of latency ad firing rate of the cells response, for understanding if these parameters influence the safety and the efficacy of the stimulation. In this paper, in order to study the propagation of the ultrasound wave from the transducer to the cortical cells, a multiscale approach was implemented by building a macroscopic model, which estimates the pressure profile in a simplified 2D human head geometry, and coupling it with the SONIC microscale model, that describes the electrical behaviour of a cortical neuron. The influence of the stimulation parameters and of the skull thickness on the latency and the firing rate are evaluated and the obtained behaviour is linked to the sensory response obtained on human subjects. Results have shown that slight changes in the transducer position should not affect the efficacy of the stimulation; however, high skull thickness leads to lower cells activation. These results will be useful for evaluating safety and effectiveness of tFUS for sensory feedback in closed-loop prosthetic systems.